Incorporating risk into technical efficiency for Vietnam’s and ASEAN banks - Ngo, Tra Thanh (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to incorporate risk in technical efficiency of ASEAN banks in a panel data framework for the period 2000 to 2015. Design/methodology/approach The directional distance function and semi-parametric framework are employed to estimate efficiency scores for two scenarios, one with only good outputs and the other with a combination of good and bad outputs. Findings The findings show there is no evidence of technological progress for banks in ASEAN and concerns about the outperformance of Vietnam’s banks. In addition, performance of Vietnam’s banks tends to be distorted by low level of loan loss reserves. Practical implications To reflect the true performance and shorten the period of removing bad assets, the State Bank of Vietnam can request banks in Vietnam to book more loan loss reserves. Originality/value By examining such a new approach, this study makes an early attempt to incorporate credit risk into the banking efficiency in ASEAN region.